An Overview of PRC's Emergence and East Asian Trade Patterns to 2020 - David Roland-Holst (Asian Development Bank Institute (ADBI), 2002)
This paper presents an empirical analysis of PRCís regional economic emergence, intended to improve longer term visibility for policy makers, helping overcome the threat-bias and better identify the horizon of opportunity for other East Asian economies. A multi-country dynamic forecasting model is used to elucidate regional and domestic adjustments that will ensue from PRCís WTO accession over the next two decades. Generally speaking, PRC growth is found to produce a variety of dramatic adjustments in East Asia, but that the benefits for every regional partner can outweigh the costs if multilateral trade policies are accommodating.
hdl:11540/4132
Keywords: 330